EFFECT OF SOLID FERTILIZER AND NPK FERTILIZER APPLICATION ON GROWTH AND YIELD OF SWEET CORN (Zea mays saccharata Sturt.) - Ikhfan Abdillah Panjaitan; Syafrizal Hasibuan; Safruddin Safruddin (Universitas Asahan, 2018)
This research was conducted on the research garden of Faculty of Agriculture University of Asahan, Kisaran Naga Village, Kisaran Timur Subdistrict, Asahan District in June to September 2017. The experiment was arranged in Randomized Complete Block Design with two factors and three replication. The first factor is 3 degree of the giving of solid fertilizer that is S0 = 0 ton/ha (0kg/plot), S1 = 10 ton /ha (1 kg/plot), S2 = 20 ton/ha (2 kg/plot), S3 = 30 ton/ha (3 kg/plot). Second factor is the giving of NPK 15–15–15 fertilizer that is N0 = 0 kg/ha (kontrol), N1 = 50 kg/ha (5 g/plot), N2= 100 kg/ha (10 kg/plot). Parameters were observed are plant height, production per plant, production per plot. The result of the research showed that solid fertilizer application haveeffect on plant height an production per plot. NPK 15–15–15 fertilizer application have effect on plant height, production per plant and production per plot. No interaction of solid fertilizer and NPK 15–15–15 fertilizer application on growht and yield of sweet corn.